Food allergies and allergens: Characterization and perceptions among diagnosed food allergic individuals in Lebanon() - Dimassi, Hani (World Allergy Organ J, 2020)
BACKGROUND: The aim of our study was to assess the knowledge, practices, and attitudes towards food allergens and allergies among diagnosed food allergic individuals in Lebanon. METHODS: Seventy diagnosed participants were recruited after reaching out to all the allergists of the country. They completed in person or over the phone a comprehensive valid questionnaire composed of 49 questions. RESULTS: Wheat was reported as top food allergen (15.7%), while itchy skin and rash were the most reported symptoms (71.4% and 68.6%, respectively). Only 34 (48.6%) of participants indicated they carry medications, 58 (70.7%) were diagnosed using blood test, and 22 (31.4%) stated that they are very knowledgeable on the topic. In terms of knowledge, participants scored on average 84.2 ± 11.5%. In terms of best practices, participants scored on average 47.8 ± 28.3%. Having a health related educational background increased significantly (p < 0.05) both knowledge and best practices scores, while age and gender did not have an effect. CONCLUSIONS: Our results highlight the importance of organizing ongoing educational initiatives and emphasize the need to lobby policy makers to making allergen-warning labels obligatory in the country.